2018
DOI: 10.1002/we.2178
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear soil‐pile interaction for offshore wind turbines

Abstract: The current work presents a parametric study, which involves different generalized nonlinear mechanical formulations with different damping characteristics to account for the interaction between a monopile-supported offshore wind turbine and the surrounding soil. The novelty of the study lies in the fact that recently developed nonlinear mechanical models used so far for the simulation of high-damping rubber isolators are introduced to describe the nonlinear hysteretic soil behavior. More specifically, the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The topics include, among others, nonlinear response of foundations and soil liquefaction and their impact on foundation performance 25 . The available computational models have been applied or extended to the dynamic analysis of monopiles in offshore wind turbines (OWT)in the past several years 26–33 . Monopiles are characterized by large diameter steel pipe sections (diameters ranging from 5 to 10 m) and relatively short length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topics include, among others, nonlinear response of foundations and soil liquefaction and their impact on foundation performance 25 . The available computational models have been applied or extended to the dynamic analysis of monopiles in offshore wind turbines (OWT)in the past several years 26–33 . Monopiles are characterized by large diameter steel pipe sections (diameters ranging from 5 to 10 m) and relatively short length.…”
Section: Introductionmentioning
confidence: 99%
“…25 The available computational models have been applied or extended to the dynamic analysis of monopiles in offshore wind turbines (OWT)in the past several years. [26][27][28][29][30][31][32][33] Monopiles are characterized by large diameter steel pipe sections (diameters ranging from 5 to 10 m) and relatively short length. With such dimensions, the monopiles approach embedded caissons which are expected to undergo considerable rotation due to the kinematic interaction during earthquake shaking.…”
mentioning
confidence: 99%
“…Their sensitivity analyses showed that water depth and wave period have important influence on the fatigue loads. Most recently, Markou and Kaynia developed a procedure for extending the non‐linear static p‐y springs to cyclic loading and implemented a procedure for limiting the damping generated by the hysteretic loops in the springs. To assess the importance of soil‐pile modelling and damping, Aasen et al carried out a parametric study in which they used four different models for the simulation of the monopile of an OWT.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of (non-linear) pile-soil interaction is not novel. Various related fields note the importance of pile-soil interaction during dynamic loading, for example, post-installation modeling of wind and wave loads (Markou and Kaynia, 2018), piles in earthquake analysis (Nogami and Konagai, 1987;Novak, 1991), pile bearing capacity under vertical vibration (Nogami and Konagai, 1987) and onshore vibratory pile driving (Holeyman, 2002). Cui et al (2022) introduce a Winkler spring connection between the pile and surrounding soil to study the effect of incomplete pile-soil bonding on the vibrations of a floating pile.…”
mentioning
confidence: 99%